Ownership Transformation and System Change in China - Bernard Chavance (Revue de la Régulation)
Compared to other post-socialist economies, the evolution of ownership forms during system change appears quite original in China. A first diversification occurred during the 1980s, with the enlargement of « non-state » (private, foreign) ownership forms ; concurrently usus and fructus rights were redistributed within unchanged legal forms of collective and state ownership. During the 1990s a wide-scale privatization process was launched both in the collective industrial sector and in the state sector. Since the 2000s, a mixed system stabilized where non-state forms predominate from a quantitative point of view, while the state sector takes the form of large business groups in the strategic sectors. The entangled character of both private and state ownership, and the connexion of these two sectors with the Party, make up the base of an original type of party-state (mixed) capitalism.